ANALISIS HIGH ORDER THINKING SKILLS(HOTS) SISWA KELAS X SMA N SE-KECAMATAN TAMPAN PEKANBARU PADA MATERI USAHA DAN ENERGI - Reski Vernando; Mitri Irianti; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to analiyze students High Order Thinking Skills in solving HOTS questions. The method used in this study in survey research to provide an overview of the patterns and levels of class X HOTS of students onbusiness and energy material. The subjects of this study were66 students in class X high school in the Tampan district of Pekanbaru.The research instrument used wasa matter of bussines and energy HOTS. Data collection techniques by providing instrument HOTS to class X students who have studied bussines and energy materials. Based on the analysis of the data it can be concluded that the instrument HOTS are able to analyze High Order Thinking Skills of class X students in all the Tampan district of Pekanbaru with an average in the unvavorable category.Key Words: HighOrder Thinking Skills Students, Test intruments HOTS, Effort and Energy